Design strategies to address kinetics of drug binding and residence time. Issue 10 (15th May 2015) - Cusack, Kevin P.; Wang, Ying; Hoemann, Michael Z.; Marjanovic, Jasmina; Heym, Roland G.; Vasudevan, Anil
Graphical abstract